Estado sistemático y distribución geográfica de Argenteohyla siemersi (Mertens, 1937) en la República Argentina (Anura: hylidae) - Williams, Jorge Daniel (1994)
Argenteohyla siemersi pederseni n. subsp. is described from the province of Corrientes, Argentina. The new subspecies is differentiated from Argenteohyla siemersi siemersi by the coloration pattern and the presence of two longitudinal black lines in the dorsum. Comments on the habitat and biogeography are added.